Adjectival Collocations for Halloween in Early 19th until 20th in COHA and COCA - Puji Rahayu (Department of Master of Linguistic, Universitas Airlangga, 2017)
AbstractKnowing the development of certain word in society and relating it with the social perspective is quite interesting. Diachronic corpus is a science in the corpus linguistics that can be used to traverse space and time. To trace the development of certain aspect of language in America, diachronic corpus can be applied by using superior corpus of the Corpus of Contemporary American English (COCA) and the Corpus of Historical American English COHA as the tools to determine the actual state of a society. Halloween is one of the celebrations which firstly celebrated in America and transmitted to be celebrated in all over the world. How Halloween is perceived in its origin country, America. This research aims to find any words that become the adjectives collocation for [Halloween] word and the perspectives about it in America in different periods of time. Employing mixed-method as approach, this research took the computerized data in COHA and COCA then interpreting the result of the adjectival collocations result. The result of this research shows that there is the changing perspective in America toward Halloween. Comparing the perspective of Halloween in the past and the current time shows that Halloween is changing overtime from religiously sacred to be fun and joyful celebration with many interesting tricks to celebrate it.